SISTEM VIRUS BATCH SEDERHANA - Fatkhiyah, Erfanti; Isa, Doddy Muhammad (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
Virus growth is currently very rapid and the type of virus that has circulated is also very diverse. One of those is a batch virus, a virus that uses simple commands in DOS. Batch virus did not differ with other viruses, only the manufacturing process does not require advanced programming language. With just some command line, virus of this type can be a simple virus that are simply annoying, or a virus that is quite dangerous. The process of making batch virus is quite simple, just disable, enable, and disable the facility in the operating system, and copying files. Examples of making batch virus of file extension exe by displaying one of the icons. Examples of simple batch virus has been created and tested into the Windows operating system, it can be quite successful, and targeted attacks are mostly Windows registry, but did not rule out also to attack the existing files, eg file documents , pictures, etc., which can cause the files are unusable, disappear, and so forth.